Analisis Nilai-Nilai Religius Pada Novel Cahaya Cinta Pasantren Karya Ira Madan - Cunayah, Ucum; Suntoko, Suntoko; Meliasanti, Ferina (Peneliti.net, 2024)
Literary works have various values, one of which is religious value. Religious values ​​are religious norms that a person adheres to as a guide to life. One form of literary work is a novel. A novel is a work of fiction with a long storyline, so there are many conflicts between various characters in it. Through Ira Madan, research conducted by researchers has research objectives, namely. (1) Describe the religious values ​​contained in the novel Cahaya Cinta Pasantren. This research uses the theory of religious values ​​put forward byjauhari. The data collection technique in this research is document study. The subject of this research is the novel Cahaya Cinta Pasantren by Ira Madan. The results of this research found religious values ​​which include: (1) aqidah; (2) worship; and (3) Morals.